Analyzing Competition In Pharmaceutical Sector – With A Case Study Of Albania - Lorena Balili (European Scientific Journal, ESJ, 2016)
Albanian pharmaceutical market is a stable and regulated market. With a status of an EU candidate country, it is essential to adopt and transpose EU directives with domestic regulation. The aim of this study is to provide a panorama regarding pharmaceutical sector, by reflecting the specific elements that influence the demand and supply of product. It will be followed by a brief description regarding three major regulatory aspects that affect the activity of companies operating in it. This study has two main pillars: Comparative analysis between Albania and Macedonia regarding the three main indicators of Health financing system; Competitiveness analysis, which consists in studying the competition between the constituent companies of the pharmaceutical sector in Albania. We calculate the fourfirm concentration ratio (CR4) and Herfindahl Hirschman Indexes (HHI). In the end we present the main findings from our study.